2021
DOI: 10.1111/1759-7714.13856
|View full text |Cite
|
Sign up to set email alerts
|

Propofol suppresses lung cancer tumorigenesis by modulating the circ‐ERBB2/miR‐7‐5p/FOXM1 axis

Abstract: Background Propofol is a commonly used anesthetic for cancer surgery. Previous studies have shown that propofol has an anticancer role in various cancers, including lung cancer. This study aimed to investigate the role of propofol in lung cancer and its underlying mechanism. Methods Cell proliferation was determined by cell counting kit‐8 (CCK‐8) and colony formation assays. Flow cytometry and transwell assays were used to detect cell apoptosis and invasion, respectively. Glycolysis was evaluated by detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…[22] Previous studies have found that circ-ERBB2 inhibiting circ-ERBB2 expression. [21] In this study, we predicted and confirmed miR-181a-5p as a target for circ-ERBB2. Consistent with previous studies, we found that low miR-181a-5p expression in CRC, and overexpression of miR-181a-5p attenuates the malignancy of CRC cells.…”
Section: Circ-erbb2 Inhibits 5-fu Sensitivity To Crc Cells Via Spongi...supporting
confidence: 63%
See 1 more Smart Citation
“…[22] Previous studies have found that circ-ERBB2 inhibiting circ-ERBB2 expression. [21] In this study, we predicted and confirmed miR-181a-5p as a target for circ-ERBB2. Consistent with previous studies, we found that low miR-181a-5p expression in CRC, and overexpression of miR-181a-5p attenuates the malignancy of CRC cells.…”
Section: Circ-erbb2 Inhibits 5-fu Sensitivity To Crc Cells Via Spongi...supporting
confidence: 63%
“…Circ-ERBB2 has been previously suggested to be related to prognosis and malignancy of a variety of tumors. [18][19][20][21] A study revealed that circ-ERBB2 is an important regulator of cancer cell proliferation, which can serve as the novel target in anti-gallbladder cancer treatment. [18] In gastric cancer, circ-ERBB2 was also found to be a potential prognostic biomarker.…”
Section: Circ-erbb2 Inhibits 5-fu Sensitivity To Crc Cells Via Spongi...mentioning
confidence: 99%
“…Cells in logarithmic growth phase (approximately the 3rd-5th generation) were used for subsequent experiments. H1299 and A549 cells were treated with 0, 5 and 10 µg/mL propofol (Sigma-Aldrich Chemical Co.) which was dissolved in dimethyl sulfoxide (DMSO, Solarbio) (Gao et al 2021), and miR-199a expression was determined at 12, 24, and 48 h, respectively.…”
Section: Culture and Propofol Treatment Of Nsclc Cellsmentioning
confidence: 99%
“…Molecular mechanisms regarding the role of propofol on cancer have been proposed. For example, propofol has been reported to suppress lung cancer tumorigenesis by modulating the circ-ERBB2/miR-7-5p/FOXM1 axis [ 14 ]. Other studies showed that propofol suppressed colorectal cancer development by the circ-PABPN1/miR-638/SRSF1 axis [ 15 ] and mediated pancreatic cancer cell activity through the repression of ADAM8 via SP1 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%